BS ISO 15632. Microbeam analysis. Selected instrumental performance parameters for the specification and checking of energydispersive X-ray spectrometers for use in electron probe microscope or an electron probe microanalyser (EPMA). (12th December 2019) - British Standards Institution,
No abstract available